1981
DOI: 10.1002/1097-0142(19810715)48:2<310::aid-cncr2820480216>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Screening for metastases in breast cancer: An assessment of biochemical and physical methods

Abstract: Ten tumor markers were measured in serum or urine at approximately three month intervals in patients with breast cancer following mastectomy but before development of overt metastatic disease. In 23 patients who later had metastases, only three markers, alkaline phosphatase, carcinoembryonic antigen (CEA), and gamma-glutamyl transpeptidase (gamma-GT) were consistently abnormal prior to the development of detectable metastases in more than one patient. In half the patients, a "lead interval" of three months or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Serial increases of these tumour markers were the first sign of recurrence in two out of every three patients with distant recurrence. These results are similar to those reported in smaller series Staab et al, 1980;Chatal et al, 1981;Coombes et al, 1981) and indicate that tumour marker determinations cannot replace other diagnostic procedures, but are useful tools in early diagnosis of recurrence. There are no studies evaluating c-erbB-2 in the early diagnosis of recurrence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Serial increases of these tumour markers were the first sign of recurrence in two out of every three patients with distant recurrence. These results are similar to those reported in smaller series Staab et al, 1980;Chatal et al, 1981;Coombes et al, 1981) and indicate that tumour marker determinations cannot replace other diagnostic procedures, but are useful tools in early diagnosis of recurrence. There are no studies evaluating c-erbB-2 in the early diagnosis of recurrence.…”
Section: Discussionsupporting
confidence: 88%
“…The usefulness of CEA and/or CA 15.3 for early detection of recurrence in breast cancer is still unclear. Some authors have indicated that elevations of CEA precede the onset of clinically detectable metastatic disease, whereas others disagree with this finding Chatal et al, 1981;Coombes et al, 1981). Sensitivity of CEA and CA 15.3 in patients with metastatic breast cancer does, however, suggest its possible role in the diagnosis of relapse.…”
mentioning
confidence: 99%
“…Plasma GGTP activity levels were determined for 230 patients with melanoma (839 assays), 132 with breast cancer (443 assays), 32 with lung cancer (96 assays), 28 with lymphoma (61 assays), and 13 with hypernephroma (33 assays). GGTP levels were also determined for I20 healthy controls (262 assays), 15 patients with systemic lupus erythematosis (28 assays), and 10 patients with rheumatoid arthritis ( 1 1 assays). The majority of patients attended hospitals and clinics at the University of Oklahoma Health Sciences Center or were seen as outpatients at the Oklahoma Medical Research Foundation.…”
Section: Methodssupporting
confidence: 79%
“…Plasma gamma-glutamyl transpeptidase (GGTP) levels were determined in 120 healthy controls, 435 cancer patients, 15 patients with systemic lupus erythematosis (SLE), and 10 patients with rheumatoid arthritis. The mean and standard error of the mean (SE) of the GGTP values from control and cancer patients are shown in Figure 1.…”
Section: Ggtp Levels In Control Und Cuncw Patientsmentioning
confidence: 99%
“…Combinations of tumour markers, including carcinoembryonic antigen (CEA), have been investigated to increase the sensitivity of detecting metastases by biological markers (Franchimont et al, 1976;Coombes et al, 1977a;Coombes et al, 1977b;Cowen et al, 1978;Cove et al, 1979;Coombes et al, 1981;Bezwoda et al, 1981). A much smaller number of studies have reported on the use of CEA in combination with other biological markers in measuring response (Woo et al, 1978;Waalkes et al, 1978;Haagensen et al, 1978;Silva et al, 1982).…”
mentioning
confidence: 99%